2010
DOI: 10.3892/ijo_00000692
|View full text |Cite
|
Sign up to set email alerts
|

Putative cancer stem cells in malignant pleural mesothelioma show resistance to cisplatin and pemetrexed

Abstract: Abstract. Malignant pleural mesothelioma (MPM) is a lethal cancer of the mesothelium with high chemotherapeutic resistance via unknown mechanisms. A prevailing hypothesis states that cancer stem cells (CSCs) persist in tumors causing relapse after chemotherapy, thus, rendering these cells as critical targets responsible for tumor resistance and recurrence. We selected candidate CSC markers based on expansion under hypoxic conditions, a hallmark for the selection of chemoresistant cells; and investigated the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…CSCs theory is based on a hierarchical organization of cells in the tumor, where only a sub-set of cells with high tumor-forming properties can give rise to a heterogenous cancerous cell population associated with rapid recurrence [ 38 , 39 ]. Different studies identified the presence of CSCs within malignant mesothelioma (MM) tissue as responsible for tumor heterogeneity [ 40 ], chemoresistance and relapse after therapy [ 41 ]. MM, as with other tumor types, is strongly characterized by inter and intra-tumor heterogeneity and the persistence of resistant CSCs in tumor tissue represent the main cause of treatment failure in cancer therapy [ 42 , 43 ].…”
Section: Mesothelioma Stem Cells (Mscs) and Chemoresistancementioning
confidence: 99%
“…CSCs theory is based on a hierarchical organization of cells in the tumor, where only a sub-set of cells with high tumor-forming properties can give rise to a heterogenous cancerous cell population associated with rapid recurrence [ 38 , 39 ]. Different studies identified the presence of CSCs within malignant mesothelioma (MM) tissue as responsible for tumor heterogeneity [ 40 ], chemoresistance and relapse after therapy [ 41 ]. MM, as with other tumor types, is strongly characterized by inter and intra-tumor heterogeneity and the persistence of resistant CSCs in tumor tissue represent the main cause of treatment failure in cancer therapy [ 42 , 43 ].…”
Section: Mesothelioma Stem Cells (Mscs) and Chemoresistancementioning
confidence: 99%